Low energy availability and impact sport participation as risk factors for urinary incontinence in female athletes. Issue 3 (June 2021) - Whitney, Kristin E.; Holtzman, Bryan; Cook, Danielle; Bauer, Stuart; Maffazioli, Giovana D.N.; Parziale, Allyson L.; Ackerman, Kathryn E.
Summary: Introduction: Relative Energy Deficiency in Sport (RED-S) is a clinical syndrome that includes the many complex health and performance consequences of low energy availability (EA) in athletes, when there is insufficient caloric intake to meet exercise-related energy expenditure and to support basic physiologic functions. There is a high prevalence of urinary incontinence (UI) in female athletes and it is more common in female athletes than non-athletes. The objective of this study was to determine if low EA is associated with UI in a population of adolescent and young adult female athletes and to evaluate for an association between sport categories and UI. Material and methods: 1000 nulliparous female patients, ages 15–30 years, presenting to a sports medicine subspecialty clinic, provided informed consent/assent to participate in a cross-sectional study involving a comprehensive survey, anthropomorphic measurements, and medical record review. Low EA was defined as meeting ≥1 criterion: self-reported history of eating disorder/disordered eating (ED/DE), and/or a high score on the Brief Eating Disorder in Athletes Questionnaire (BEDA-Q), and/or a high score on the Eating Disorder Screen for Primary Care (ESP). UI was assessed using questions adapted from the International Consultation on Incontinence-Urinary Incontinence Short Form (ICIQ-UI-SF), questions regarding timing of UI onset/duration, and a binary question regarding UI during sport activities. A total of 36 sport types were included in the survey and sub-divided into categories. Results and discussion: Of the 1000 female athletes surveyed, 165 (16.5%) reported a history of experiencing UI during athletic activities. ICIQ- UI-SF responses indicated that 14% (137/1000) of the cohort experienced slight incontinence, 4% (35/1000) moderate incontinence, and 2 athletes experienced severe incontinence. There was a significant difference between UI categories in age (p = 0.01), low EA (p < 0.001), and sport category (p < 0.001). Females who had low EA had twice the likelihood (OR = 1.97; 95% CI = 1.39 to 2.81; p < 0.001) of UI compared to those with adequate EA, controlling for sports category and menstrual dysfunction. Females who participated in high impact sports were 4.5 times more likely (OR = 4.47; 95% CI = 2.29 to 8.74; p < 0.001) to have had UI compared to females who participated in ball sports, controlling for EA and menstrual dysfunction. Conclusions: UI during athletic activities is a common problem among nulliparous adolescent and young adult female athletes, occurring in 16.5% of female athletes surveyed. UI was significantly associated with low EA across all sport categories. Sport type was significantly associated with UI, with the highest impact sport group demonstrating a higher prevalence and symptom severity compared to other sport categories. Summary Table Characteristics of Female Athletes with Urinary Incontinence Summary Table   Entire cohort N = 1000 Athletes with Urinary incontinence n = 165 (16.5%) P-value Freq. (%) Freq. (%) Low energy availability 473 (47%) 99 (20.9%) <0.001 Menstrual dysfunction 449 (45%) 80 (17.8%) 0.31 Sport category:         <0.001  High impact 49 (5%) 18 (36.7%)    Ball/field 356 (36%) 46 (12.9%)    Non-weightbearing endurance 60 (6%) 6 (10.0%)    Aesthetic 173 (17%) 25 (14.5%)    Resistance/power 106 (11%) 23 (21.7%)    Running 222 (22%) 44 (19.8%)    Technical 34 (3%) 3 (8.8%)